2000
DOI: 10.1046/j.1365-2435.2000.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial processes and carbon‐isotope fractionation in tropical and temperate grassland soils

Abstract: Summary 1.The carbon content and δ 13 C value of soil organic carbon (SOC), microbial biomass (C mic ) and respired CO 2 were measured in a range of grassland soils from tropical and temperate biomes to determine if isotope effect of microbial degradation can induce a shift in isotope composition of SOC and CO 2 . The soil from a depth of 0-2 cm was analysed. C mic was measured using the chloroform fumigation extraction method, while CO 2 was measured in a closed system after 3 and 10 days of incubation. Two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(100 citation statements)
references
References 35 publications
3
94
1
2
Order By: Relevance
“…This hill range is situated about 20 km NW of Zurich (47 • 28 40.8 N, 8 • 21 55.2 E) and belongs to the easternmost part of the Jura mountain range. As a contribution to the CarboEurope IP, netecosystem CO 2 exchange and soil respiration have been measured routinely there for several years (Etzold et al, 2010;Ruehr et al, 2010). The mean annual temperature is 8.4 • C and mean annual precipitation is 930 mm.…”
Section: Study Site Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…This hill range is situated about 20 km NW of Zurich (47 • 28 40.8 N, 8 • 21 55.2 E) and belongs to the easternmost part of the Jura mountain range. As a contribution to the CarboEurope IP, netecosystem CO 2 exchange and soil respiration have been measured routinely there for several years (Etzold et al, 2010;Ruehr et al, 2010). The mean annual temperature is 8.4 • C and mean annual precipitation is 930 mm.…”
Section: Study Site Descriptionmentioning
confidence: 99%
“…How much the aboveground litter contributes to the soil C pool in the long term depends considerably on the rate at which its C is either mineralised to CO 2 or incorporated into mineral soils through soil fauna and dissolved organic C (DOC) (Rubino et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about isotopic effects of C transfer in soil through the microbial community. Recent studies revealed that δ 13 C values of microbial biomass were 13 C enriched by about −2‰ relative to that of the corresponding total soil C, indicating that an isotope effect due to microbial degradation may also be of importance in soil (Angers et al 1995;Santruckova et al 2000). The authors concluded that this isotope effect could be induced by selective assimilation of different soil C pools or 13 C fractionation during microbial metabolism, in particular during respiration where the released CO 2 is depleted in 13 C. It is extremely difficult to obtain microbial C from soil because of the likelihood of co-extracting material from indigenous soil C (Sparling et al 1990), resulting in an inaccurate determination of δ 13 C values.…”
mentioning
confidence: 99%
“…Third, many studies have indicated that fractionation by microorganisms results in SOC  13 C enrichment with depth (Agren et al 1996;Schweizer et al 1999;Santruckova et al 2000;Powers and Schlesinger 2002). Microorganisms preferentially metabolize molecules containing the lighter 12 C, so that the remaining SOC tends to be 13 C enriched.…”
Section: Vertical Patterns Of Soc D 13 C Of High and Middle Tidal Manmentioning
confidence: 99%